Investigation of the effects of probiotics on allergy - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2018)
Objectives: To investigate the effects of a probiotic mixture that was isolated from human gut flora, and a standard probiotic strain Lactobacillus GG (LGG) on allergic immune responses in an animal model. Materials and Methods: Three Enterococcus faecalis, 8 Lactobacillus plantarum, and 2 Lactobacillus rhamnosus strains were included in the mixture. Balb-c mice in the study groups were given the probiotic mixture, and standard strain LGG, and animals in the control groups were given skimmed milk for 28 days. The mice in the study groups and the positive control group were immunized with an intraperitoneal injection of ovalbumin (OVA) on days 14 and 21. An enzyme-linked immunosorbent assay was used to study the OVA-specific IgE levels in the mice serums. Results: The most remarkable results were that OVAspecific IgE levels were significantly higher (P<0.001) in the positive control group compared with the nonimmunized negative control group, and OVA-specific IgE levels in the study groups were significantly lower than the positive control group (P<0.001). Conclusion: The data of the present study suggest that oral administration of probiotics prevents IgE-mediated OVA-hypersensitivity; however, the immunoregulatory effects of strains must be described in detail while preparing probiotic mixtures.
Keywords: Probiotics; Hypersensitivity; Lactobacillus; LACTOBACILLUS-RHAMNOSUS GG; FOOD ALLERGY; IMMUNE-RESPONSES; BALB/C MICE; PREVENTION; MODEL; INTERLEUKIN-10; PLANTARUM; CHILDREN; BACTERIA